2018
DOI: 10.1002/ppul.23956
|View full text |Cite
|
Sign up to set email alerts
|

Role of prophylactic azithromycin to reduce airway inflammation and mortality in a RSV mouse infection model

Abstract: Prophylactic azithromycin effectively reduced weight loss, airway inflammation, cytokine levels and mortality in RSV-infected mice. These results support the rationale for future clinical trials to evaluate the effects of prophylactic azithromycin for RSV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
0
24
0
3
Order By: Relevance
“…Therefore, it is necessary to find low-toxic and effective drugs to treat excessive inflammation caused by virus. The excessive inflammation caused by RSV infection is worthy of attention (Shi et al, 2016;Mosquera et al, 2018). There is growing evidence that certain natural products may be able to keep mice away from viral pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary to find low-toxic and effective drugs to treat excessive inflammation caused by virus. The excessive inflammation caused by RSV infection is worthy of attention (Shi et al, 2016;Mosquera et al, 2018). There is growing evidence that certain natural products may be able to keep mice away from viral pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…A variety of animal models exist to research respiratory viruses such as influenza [124][125][126], RSV [127][128][129][130][131][132][133][134][135][136][137], HRV [22,[138][139][140]. No single animal offers a platform for all respiratory viruses that infect humans, and different animal models exist for the same virus, which can give different, often conflicting results.…”
Section: The History Of the Human Viral Challenge Modelmentioning
confidence: 99%
“…We predict that the prophylactic use of azithromycin will reduce the morbidity associated with respiratory viral infections during the winter season in patients with CLD as evidenced by a reduction in the days with unscheduled face-to-face provider encounters based on the preliminary results from our laboratory study that indicated that prophylactic azithromycin can effectively reduce airway inflammation and disease severity in a RSV-infected mouse model. 6 7 Recent studies have shown that the high morbidity rate of respiratory virus infections is a result of a neutrophilic overactive inflammatory response. 5 Macrolides downregulate the inflammatory cascade, attenuate excessive cytokine production in viral infections and may reduce virus-related exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Recent studies, including a study performed in our laboratory with elderly BALB/c mice infected with respiratory syncytial virus (RSV), have shown that the high mortality rate of respiratory virus infections is a result of an overactive neutrophilic inflammatory response. 6 7 A recently published study examined the inflammatory response in hospitalised infants with RSV and evaluated the predictive value of cytokines in nasopharyngeal aspirate in comparison to disease severity and found an increase in Th1 and Th2 cytokines. 8 Respiratory viral infections are characterised by the appearance of cytokine storms which involve an extreme production and secretion of numerous proinflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%